Pengaruh Kompensasi, Tekanan Pekerjaan dan Sistem Pengendalian Internal Terhadap Fraud Intensi di Instansi Pemerintahan - Utama, Rifky Genta; Herawansyah, Herawansyah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This study aims to examine the effect of compensation, job pressure, and internal control systems on fraud intention in government institutions in Rejang Lebong Regency. Fraud in the public sector remains a serious issue, particularly at the regional level, and therefore requires further analysis. This research employs a quantitative approach using primary data collected through questionnaires distributed to 67 respondents selected by purposive sampling. Data were analyzed using multiple linear regression with SPSS version 25. The results indicate that compensation has no significant effect on fraud intention, job pressure has a negative and significant effect on fraud intention, while the internal control system has a positive and significant effect on fraud intention. Simultaneously, the three variables have a significant influence with an Adjusted R² value of 0.646, meaning that 64.6% of the variance in fraud intention can be explained by the model, while the remaining 35.4% is influenced by other factors outside this study. These findings suggest that fraud intention in government institutions is more strongly affected by job pressure and the effectiveness of internal control systems rather than compensation.